L'étendard et le glaive : archéologie de la propriété intellectuelle en matière de mode - Blanche, Geraldine (Institut d'études politiques de Paris - Sciences Po, 2026)
Cette thèse propose une archéologie juridique de la rencontre entre la mode et la propriété intellectuelle en France. Elle étudie la manière dont la mode, objet à la fois culturel, économique et symbolique, est progressivement devenue un objet légitime de droit. L’enjeu n’est pas de dresser un manuel des protections applicables, mais de comprendre quand, comment, par quels acteurs et à quelles fins le secteur de la mode s’est saisi de la propriété intellectuelle. L’hypothèse centrale est que, dans l’industrie de la mode, la propriété intellectuelle ne se borne pas à protéger une valeur préexistante : elle contribue aussi à la produire, à la consacrer et à la convertir. Le droit apparaît ainsi à la fois comme un instrument de reconnaissance symbolique, un outil de lutte contre la copie et la contrefaçon, mais aussi un support d’exploitation économique, par la licence, l’organisation de la diffusion et la transformation des droits en actifs stratégiques.La première partie, L’étendard, montre comment le droit d’auteur, les dessins et modèles et le droit des marques ont servi à légitimer la mode comme œuvre, création industrielle et signe distinctif. La seconde, Le glaive, analyse la propriété intellectuelle comme instrument d’action dans un marché structuré par la copie, la concurrence et la valorisation des actifs immatériels. La thèse met ainsi en évidence la double portée de la propriété intellectuelle dans la mode : vecteur de reconnaissance, mais aussi levier de valorisation, de circulation maîtrisée et de capitalisation. This dissertation offers a legal archaeology of the encounter between fashion and intellectual property in France. It examines how fashion, as a cultural, economic, and symbolic object, gradually became a legitimate subject of law. Rather than providing a practical guide to the available forms of protection, it seeks to understand when, how, by whom, and for what purposes the fashion sector turned to intellectual property.Its central hypothesis is that, in the fashion industry, intellectual property does not merely protect pre-existing value; it also helps produce, consecrate, and convert it. Law thus appears both as an instrument of symbolic recognition, a tool in the fight against copying and counterfeiting, and a means of economic exploitation through licensing, the organization of circulation, and the transformation of rights into strategic assets.The first part, The Banner, shows how copyright, design law, and trademark law served to legitimize fashion as work, industrial creation, and distinctive sign. The second, The Blade, analyzes intellectual property as an instrument of action in a market structured by copying, competition, and the valorization of intangible assets. The dissertation thus highlights the dual reach of intellectual property in fashion: a vector of recognition, but also a lever for valorization, controlled circulation, and capitalization.
Issue: 2026IEPP0012
Keywords: Droit (histoire); Droit de la propriété intellectuelle; Fashion industry; France; Histoire du droit; Industrie de la mode; Industrie et commerce; Intellectual property law; Legal history; Mode; Propriété intellectuelle; Protection strategies; Stratégies de protection

Le consentement en droit de la propriété littéraire et artistique - Dramé, Mamadouba (Université de Lorraine, 2025)
Le processus d'autonomisation du droit de la propriété intellectuelle par rapport au droit commun en France a atteint son apogée à travers la loi n° 92-597 du 1re juillet 1992 qui créa un code en la matière. Depuis cette date, la matière n'a cessé de se développer. Et cette évolution n'est pas sans conséquence sur le consentement des différents acteurs du secteur. Il est question du consentement à tous les niveaux : que ce soit sur les opérations juridiques (cession, licence, contrat d'édition etc.) dont les œuvres font objet ou encore sur la volonté affichée par le législateur de protéger l'auteur ou le créateur de toute œuvre de l'esprit. L'objectif de cette thèse est donc de démontrer les manifestations du consentement de l'auteur ainsi sa particularité par rapport au droit commun. The process of making intellectual property law autonomous from common law in France reached its apogee with Law no. 92-597 of July 1, 1992, which created a code on the subject. Since then, the field has gone from strength to strength. And this evolution is not without consequences for the consent of the various players in the sector. Consent is an issue at every level, from the legal transactions (assignment, licensing, publishing contracts, etc.) to which works are subject, to the legislator's desire to protect the author or creator of any work of the mind. The aim of this thesis is therefore to demonstrate the manifestations of the author's consent, and how it differs from common law.
Keywords: Artificial Intelligence; Consent; Consentement (droit); Contract; Contrat; Contrefaçon; Copyright; Copyright infringement; Droit d'auteur; Exceptions aux droits d'auteur; Exceptions to Copyright; Intellectual property; Intelligence artificielle; Propriedade intelectual; Propriété intellectuelle

L’œuvre libre : essai d'analyse contractuelle - Chevallier, Adélaïde (Université de Bordeaux, 2025)
L’oeuvre libre, aussi connue sous le nom d’open source, est une création protégée par le droit d’auteur, mais dont l’exploitation est ouverte à tous. Si l’expression reste à ce jour peu connue du grand public, les oeuvres libres sont désormais un incontournable des pratiques quotidiennes, en attestent le succès de l’encyclopédie en ligne Wikipédia et l’attrait croissant pour les logiciels libres tels Linux, OpenOffice ou la plateforme Moodle. Malgré son essor, le phénomène du libre demeure juridiquement peu, voire mal, appréhendé. De surcroît, sa licéité fait régulièrement l’objet de contestations doctrinales, l’oeuvre libre s’inscrivant à rebours des règles traditionnelles du droit français, selon lesquelles les biens sont intangibles, non numériques et réservés à l’usage exclusif de leur titulaire. La finalité de l’étude consiste dès lors à démontrer qu’en dépit de son caractère disruptif, l’oeuvre libre peut en l’état intégrer l’ordre juridique français au moyen d’une analyse contractuelle. The concept of the “free cultural work,” also referred to as open source, designates a creation protected by copyright yet made available for use by all. While the expression remains relatively unfamiliar to the general public, free cultural works have become indispensable in contemporary practice, as illustrated by the success of the online encyclopedia Wikipedia and the growing appeal of free software such as Linux, OpenOffice, and the Moodle platform. Notwithstanding this expansion, the legal phenomenon of free cultural works continues to be only partially, if not inadequately, addressed. Furthermore, its legitimacy is the subject of recurrent doctrinal debate, insofar as the free cultural work stands in contrast to the traditional principles of French law, according to which property is tangible, non-digital, and reserved for the exclusive use of its owner. The purpose of this study is therefore to demonstrate that, despite its disruptive character, the free cultural work may, in its current form, be accommodated within the French legal order through contractual analysis.
Keywords: Contract law; Contrat; Copyright; Droit d'auteur; Free cultural works; Free license; Free software; Intellectual property; Licence libre; Logiciel libre; Oeuvre libre; Open source; Propriété intellectuelle

Contribution à l’étude de la réservation des utilités des données numériques - Grave-Renaud, Gonzague (Université de Lille, 2025)
La dématérialisation et la numérisation croissantes de notre économie ont élevé les données au rang de matière première indispensable. La valeur des données réside dans leurs exploitations potentielles. C’est pourquoi leurs détenteurs cherchent à maximiser leurs revenus en limitant l’accès. Ce constat souligne les enjeux de gouvernance des données. La problématique de la réservation des données a alors émergé. Le constat est que la propriété intellectuelle ne parvient pas à appréhender pleinement la donnée. Néanmoins, l’analyse du droit positif révèle l’existence de mécanismes du droit commun permettant une réservation des utilités des données, tels que le contrat, la concurrence déloyale et parasitaire et le secret des affaires. Bien que ces mécanismes offrent une réservation, ils ne sont pas exempts de lacunes. Aussi, la question de la propriété des données a émergé et a suscité un vif débat. Cette interrogation a engendré un renouvellement des approches théoriques et pratiques du droit de propriété. Dans une approche prospective, un droit exclusif d’exploitation sur les données a été esquissé sous la forme d’un droit sui generis. Cet exercice de conceptualisation a mis en exergue les difficultés que pourrait entraîner une telle reconnaissance. Par ailleurs, il est impératif de trouver un juste équilibre entre la volonté d’appropriation des données et le droit d’accès des tiers à celles-ci afin d’instaurer un régime de protection à la fois efficace et équitable.
Keywords: Biens incorporels; Brevets d'invention; Contrats; Data; Données; Droit d'auteur; Droit des affaires; Droit d’accès; Intellectual property; Investissements; Investments; Propriedade intelectual; Propriété; Propriété intellectuelle; Protection de l'information (informatique) – Droit; Reservation; Responsabilité (droit); Right of access; Réservation; Secret; Systèmes d'information; Valeur; Value

Le droit processuel appliqué au contentieux des brevets à l'aune de la Juridiction unifiée du brevet : quel rôle pour la Cour de justice de l’Union européenne ? - Lawrynowicz-Drewek, Anna (Université de Strasbourg, 2024)
La Juridiction unifiée du brevet (JUB), une nouvelle juridiction internationale spécialisée dans le contentieux des brevets européens, est soumise au respect du droit de l’Union européenne. Ce dernier, toutefois, demeure éparpillé et incomplet en matière de la procédure civile. La question du rôle effectif de la CJUE dans l’interprétation des règles procédurales de la JUB représente un intérêt majeur. Or, l’analyse approfondie des règles européennes et celles propres à la JUB conduisent au constat que ce rôle demeure à ce jour limité. L’absence de renforcement du rôle de la CJUE conduit à un risque de l’incohérence du droit de l’UE, de son application non uniforme ainsi que, de point de vue stratégique, à un forum shopping prononcé réduisant l’attractivité de la nouvelle juridiction spécialisée. Pour remédier à cette situation, la thèse suggère une série des propositions visant à renforcer le rôle de la CJUE en la matière, tantôt à travers des instruments horizontaux que spéciaux.
Keywords: Brevet européen; Brevet européen à effet unitaire; Brevets d'invention; Contentieux civil; Contentieux d'entreprise; Contentieux des brevets; Contrefaçon de brevet; Droit de procédure civile; Droit international privé; Droit processuel; Droits de l’Homme; Garanties procédurales; Juridiction internationale; Juridiction spécialisée; Juridiction unifiée du brevet; Union européenne (droit)

La transversalité en droit de la propriété intellectuelle - Armand-Toureuh, Rebecca (Université Paris-Saclay, 2024)
Le droit de la propriété intellectuelle, derrière l'apparence unitaire que livre le singulier de cette qualification, est, en réalité, un droit constitué d'une pluralité de régimes juridiques, tels que le droit d'auteur et ses droits voisins, le droit des dessins et modèles, le droit des signes distinctifs, ou encore le droit des brevets. À première vue, cette pluralité de droits ne répond à aucune cohérence d'ensemble.Des raisons historiques peuvent expliquer la disparité actuelle : chaque droit de propriété intellectuelle étant apparu de manière isolée, chacun d'entre eux a développé sa propre logique. Bien que le Code de la propriété intellectuelle rassemble ces différentes protections sous une qualification unitaire et les présente de manière organisée, il ne contient pas de dispositions communes. Au demeurant, l'adoption progressive de différentes protections, telles que le droit sui generis sur les bases de données, le droit d'auteur sur les logiciels, ou encore les droits voisins des éditeurs de presse, réinterrogent sans cesse les frontières de la matière.Pour tenter d'en rétablir la cohérence, la transversalité, qui s'entend d'une approche transversale, peut être mobilisée afin de se demander si, à la lumière des éléments de transversalité identifiés, ceux-ci sont susceptibles de contribuer à l'élaboration d'une théorie générale de la propriété intellectuelle.Ces éléments communs aux différents droits de propriété intellectuelle sont recherchés sous l'angle, d'abord, de l'objet du droit, puis du régime juridique pour, enfin, appréhender leur influence sur la nature juridique du droit de la propriété intellectuelle. En ce qui concerne l'objet du droit, si l'approche transversale permet de révéler certains critères de définition transversaux, elle ne permet pas de dégager une qualification unitaire de l'objet de propriété intellectuelle. S'agissant du régime juridique, l'approche transversale permet, là encore, la mise en exergue d'éléments transversaux qui sont prompts à définir un régime commun de la propriété intellectuelle, mais ces éléments se limitent au volet patrimonial du droit et à sa sanction. L'ensemble de ces éléments de transversalité, susceptibles de constituer le « noyau dur » de la propriété intellectuelle peuvent, enfin, permettre de porter un autre regard sur la nature juridique du droit de la propriété intellectuelle, en interrogeant de manière systémique sa qualification propriétaire. Behind the unitary appearance of this singular term, intellectual property law is actually made up of a plurality of legal regimes, such as copyright and related rights, design rights, trademark law and patent law. At first glance, this plurality of rights does not reflect any overall coherence.Historical reasons may explain the current disparity: each intellectual property right having emerged in isolation, each has developed its own logic. Although the French Intellectual Property Code groups these different types of protection under a single title and presents them in an organized manner, it does not contain any common provisions. In fact, the gradual adoption of different forms of protection, such as sui generis rights for databases, copyright for software, or related rights for press publishers, is constantly reexamining the boundaries of this field.In an attempt to re-establish coherence, transversality, which is understood as a transversal approach, can be mobilized to ask whether, in the light of the elements of transversality identified, these are likely to contribute to the development of a general theory of intellectual property.These elements, which are common to the various intellectual property rights, are examined first from the point of view of the object of the right, then from the point of view of the legal regime and, finally, from the point of view of their influence on the legal nature of intellectual property law. With regard to the object of the right, while the transversal approach reveals certain transversal definition criteria, it does not allow us to identify a unitary qualification of the object of intellectual property. With regard to the legal regime, the transversal approach once again brings to light transversal elements that are likely to define a common intellectual property system, but these elements are limited to the patrimonial aspect of the right and its sanction. All these transversal elements, which are likely to constitute the “hard core” of intellectual property, may finally enable us to take another look at the legal nature of intellectual property law, by systemically questioning its proprietary qualification.
Keywords: Intellectual property; Interdisciplinarité; Propriedade intelectual; Propriété intellectuelle; Transversality; Transversalité; Unity; Unité

Protection des œuvres littéraires et artistiques dans l'environnement numérique dans l'espace OAPI - Ouedraogo, Peingdeweindé Jean (Université Lumière Lyon 2, 2024)
Les technologies de l’information interrogent la propriété littéraire et artistique de façon permanente. Chaque changement technologique entraine d’importantes répercussions dans la manière de protéger les œuvres culturelles. C’est ainsi qu’avec le développement du numérique des années 2000, plusieurs législations ont été mises à jour en commençant par le droit international. L’accord de Marrakech adopté par l’OMC le 15 décembre 1994 et les deux traités de l’OMPI de 1996 à savoir le traité de l’OMPI sur le droit d’auteur et le traité de l’OMPI sur les interprétations et exécutions et les phonogrammes sont les fruits de ces mutations. Au niveau régional et national, on pourrait également citer le Digital Millénium Copyright Act de 1998 pour l’Amérique et la Directive européenne sur la société de l’information de 2001 pour ce qui est de l’Union Européenne. Tenant compte de ces changements au niveau international et dans les ordres juridiques voisins, le législateur africain a opéré une révision de l’Accord communautaire le 15 décembre 2015. Cette révision prend cependant insuffisamment en compte les préoccupations suscitées par la technologie numérique. L’exemple le plus emblématique est l’occultation des influences de l’Intelligence artificielle sur la propriété littéraire et artistique. Cette thèse vise donc à proposer des solutions pour parachever l’adaptation du droit OAPI de sorte qu’il soit à jour des standards internationaux et tienne compte des développements du droit régional dont la construction est initié par l’Union Africaine avec la mise en place de l’Organisation Panafricaine de la Propriété Intellectuelle. (OAPI). Cette étude touchant à la fois le droit matériel et le système institutionnel de l’OAPI a eu pour objectif de renforcer davantage la sécurité des intérêts des titulaires de droits et ceux des utilisateurs de leurs œuvres de sorte à rendre le cadre communautaire africain plus équilibré et sécurisé.
Keywords: AI; Acte de Bamako; Adaptation; African Regional Intellectual Property Organization; Afrique; Artificial Intelligence; Bamako Act; Copyright; CyberSpace; Cyberspace; Droit d’auteur; Inteligência artificial; Intellectual property; Intelligence Artificielle; Internet; Organisation Panafricaine de la Propriété intellectuelle; Organisation africaine de la propriété intellectuelle; Pan-African Intellectual Property Organization; Propriété intellectuelle (droit international)

La structuration de l'e-sport, étude en droit du numérique et de la propriété intellectuelle - Guedes, Emeline (Université Paris-Saclay, 2024)
L'e-sport est actuellement en phase de développement économique constant. Toutefois, au regard de la nouveauté de la pratique, le cadre juridique peine parfois à s'adapter afin de rendre la pratique e-sportive pérenne économique et stable au regard de son cadre juridique. Il est dès lors important de structurer juridiquement l'e-sport afin de lui offrir un cadre économique solide. Cette pratique spécifique appelle une structuration par le droit du numérique et le droit de la propriété intellectuelle, cette recherche consiste ainsi à trouver un modèle pérenne de cadre juridique pour l'e-sport en s'inspirant de régimes déjà existants (droit du sport, de la propriété intellectuelle, de la concurrence ou encore droit de l'audiovisuel entre autres) afin que la pratique se développe sans entrave économique et par le prisme des technologies numériques en constante évolution. Cette recherche fait appel à des mécanismes déjà existants en droit, à des règlementations déjà applicables mais aussi à l'aménagement de nouvelles règles de droit, adaptées à la pratique e-sportive.
Keywords: Competencia; Competition; Competition law; Concurrence; Digital; Droit des technologies de l'information et de la communication; E-Sport; Esports; Intellectual property; Liability; Médias numériques; Numérique; Propriedade intelectual; Propriété intellectuelle; Responsabilité; Sport électronique

L'interopérabilité comme outil de la régulation asymétrique des marchés numériques - Martin-Lafay, Florent (Université Paris 1, 2024)
La concentration des marchés numériques autour d’une poignée d’opérateurs de plateforme numérique structurante, notion développée dans l’étude, tend à soulever des problèmes économiques et sociétaux. En matière de concurrence, en premier lieu, de nombreux économistes ont mis en exergue les défaillances des marchés sur lesquels interviennent ces acteurs (i.e. effets de verrouillage tels que les effets de réseau et la capture des données, économies d’échelle et d’envergure) ainsi que les effets néfastes pour la liberté de choix des utilisateurs et l’innovation. Les problèmes de concurrence interplateforme et intraplateforme s’accompagnent de problèmes plus sociétaux liés à la concentration des flux d’information autour des écosystèmes construits par ces opérateurs et au sein desquels les utilisateurs sont maintenus captifs. Les opérateurs de plateforme numérique structurante ont acquis une position incontournable sur l ’internet leur conférant un rôle de quasi-régulateur des activités en ligne. Cette situation tend à affaiblir la liberté d’expression et d’information des utilisateurs, leur liberté d’association et liberté de réunion ainsi que leur droit au respect de la vie privée. Fort de ce constat, qui a appelé de nombreuses réponses législatives de la part des pouvoirs publics, en Europe particulièrement, l’étude analyse plus spécifiquement l’interopérabilité comme un outil permettant, lorsque c’est nécessaire et proportionné, d’ouvrir les écosystèmes des opérateurs de plateforme numérique structurante afin de promouvoir la liberté de choix des utilisateurs, la concurrence et l’innovation. Raisonnant par analogie avec le droit des communications électroniques ainsi que d’autres régimes ayant mis en place ce type de remède d’accès (e.g. droit de la concurrence, règlement sur les marchés numériques, droit bancaire, droit des transports), les bénéfices de l’interopérabilité pour renforcer l’autonomie des utilisateurs sont mis en exergue. L’étude s’intéresse aussi aux implications de l’adoption d’un tel remède en droit positif et son effet notamment sur les droits des débiteurs (e.g. propriété intellectuelle) et des tiers concernés (e.g. vie privée). Elle s’intéresse également aux difficultés de mise en œuvre de l’interopérabilité qui comporte une forte dimension technique et qui serait amenée à être imposée sur des marchés présentant d’importantes asymétries d’information. S’inspirant des solutions dégagées au sein de différents instruments juridiques, l’étude propose des pistes pour assurer une application efficace du remède.
Keywords: Communications électroniques; Competencia; Concurrence; Digital platform; Droit d'auteur et informatique; Ecosystems; Intellectual property; Interoperability; Interopérabilité; Numérique; Ouverture; Plateforme; Propriedade intelectual; Propriété intellectuelle; Technologies de l'information et de la communication – Droit – France; Écosystème

Genişletilmiş toplu lisanslama - Erçal, Hi̇lal (Ankara Yıldırım Beyazıt Üniversitesi, 2024)
Teknolojik ilerlemenin bir sonucu olarak internet, telif hakkına konu fikri ürünlerin dağıtımının yapıldığı ana mecra haline gelmiştir. Dijital teknolojinin birçok yerde ve çok yönlü birçok kişi ya da kurum tarafından kullanılması, özellikle telif haklarına konu fikri ürünleri etkilemiştir. Avrupa Birliği (AB) ise Dijital Tek Pazar oluşturma stratejisi kapsamında düzenlemelerine 2019/790 sayılı Dijital Tek Pazarda Telif Hakları ve Bağlantılı Haklar Yönergesini eklemiştir. Söz konusu direktifin 8 ve 12. maddelerinde ise genişletilmiş toplu lisanslama (GTL) düzenlenmiştir. GTL özellikle kitlesel olarak dijital mecrada kullanımın yoğun olduğu müzik, işitsel-görsel, sinema vb. eserlerin teliften arındırılmış şekilde kullanılmasına olanak sağlayan bir sistemdir. Özellikle televizyon yayınlarında olduğu gibi bazı kullanımların çok miktarda eser veya telif unsuru içermesi nedeniyle, tüm hak sahipleri ile görüşülerek kullanım izinlerinin alınması dijitalleşen dünyada hem çok maliyetli hem de oldukça zahmetli ve hatta çoğu zaman imkânsız bir hal almaktadır. Fikri ürünler üzerinde hak sahibi olanların, telif haklarını kullanma yetkisini herhangi bir meslek birliğine ya da toplu hak takibi yapan bir organizasyona vermemesi, başka bir deyişle oranın bir üyesi olmaması halinde söz konusu kullanımlar için izin alınması hem kullanıcılar açısından oldukça külfetli, hem de hak sahiplerinin menfaatlerini koruma noktasında daha da büyük bir sorun teşkil etmektedir. Bunun yanında kültürel mirasın korunmasıyla yükümlü olan kurumlar açısından en önemli zorluklardan biri, telif hakkı sahiplerinin kimliklerinin belirlenmesi ve telif hakkı içeren eserlerin kullanılması için yetki ya da lisans alınması gibi telif hakkı temizliğine ilişkin süreçlerdir. Özellikle sınır ötesi online kullanımlar açısından düşünüldüğünde bu çok daha karmaşıktır. GTL düzenlemesi ile dijital çağda herhangi bir toplu hak yönetimi organizasyonuna üye olmayan eser ve bağlantılı hak sahipleri açısından da meslek birlikleri ile kullanıcılar arasında yapılan lisans sözleşmelerinin geçerli olmasını sağlayacak bir sistem öngörülmüştür. As a conclusion of technological progress, the Internet has named as the main channel where the intellectual products subject to copyright are distributed. The use of digital technology by many people or institutions in many places and in many ways has especially affected the products that are subject to copyright. On the other hand The European Union (EU), within the scope of the Digital Single Market creation strategy, has added the Digital Signal Market Directive EC 2019/790 to its regulations. Extended Collective Licensing (ECL) is regulated in 8th and 12th articles of the mentioned directive. ECL is a system that enables the copyright permisson obtained use of works such as music, audio-visual, cinema, etc., which are massively used in digital media. As some uses especially like television broadcasts include a large amount of copyright items or works, in the digitalized world, it becomes costly as well as tough and even imposibble obtaining authorisations from right-holders by negotiating with all of them. If the rightholders of the intellectual products don't give authorisation of the exercise of their rights to a collecting society in another words, ıf they are not member of this organisation, obtaining permission for such uses would be very hard and transaction costs would be very high for the users and creates a greater issue as for the protection of benefits of the right-holders. Besides that the largest copyright challenge for Cultural Heritage Instutitions is the process of identification of right holders of copyright and clearence of rights, i.e obtaining authorization of licences for use of in-copyright works. When it's considered for cross-border online uses, it is more complex. In the digital age with the regulation of ECL, a system has been predicted to ensure that the licence agreements made between collecting societies and users are valid for authors and related-right holders who are not members of any collective rights management organisations.
Tez N°892117
Keywords: Copyright; Extended Collective Licensing; Extended Effect; Genişletilmiş Etki; Genişletilmiş Toplu Lisanslama; Intellectual property; Telif Hakkı

الحماية الجزائية للعالمة التجارية بين التشريع الجزائري و التشريع المغربي - دراسة مقارنة - صافو, سارة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص تهدف هذه الدراسة بتحميل ومقارنة الحماية الجزائية من الجرائم الماسة بالعالمة التجارية في الجزائر والمغرب، في هذا الصدد تهدف الدراسة إلى معرفة األهمية االقتصادية التي تكتسيها العالمة التجارية محل الحماية و أثر الجرائم الواقعة عميها عمى االقتصاد الوطني لمبمدين، خاصة في ظل اتجاه الجزائر والمغرب نحو تبني اقتصاد مبني عمى المعرفة القائم عمى اإلبداع واالبتكار. في البداية، وبعد التطرق لألحكام المنظمة لمعالمة التجارية من خالل توضيح مدى توافق التشريعين، تعني الد ارسة بتحميل ومقارنة طبيعة القانونية لمعالمة التجارية من ضبط مفهومها إلى اكتساب الحق فيها، عن طريق توضيح أهميتها كمؤشر لقياس االقتصاد الوطني. تنتقل الد ارسة لتبين تدخل المشرعين الج ازئري والمغربي بوضع آليات حمائية قبمية وبعدية لردع الج ارئم الواقعة عمى العالمة التجارية، تتفحص الدراسة هنا، دور اإلجراءات التحفظية ودعوى التقميد كآلية لحماية القانونية لمعالمة التجارية بهدف حماية االقتصاد الوطني. وانطالقا من القسمين السابقين لمدراسة، تحاول هذه األخيرة توضيح بعض التوجهات االقتصادية التي انتهجتها كل من الجزائر والمغرب من اقتصاد تقميدي إلى اقتصاد مبني عمى المعرفة، وأن اإلشكال المطروح في مثل هكذا ظروف جديدة يكمن في مدى ارتباط حماية العالمة التجارية بحماية االقتصاد الوطني، تبين الدراسة في هذا الشأن أن اختالف حماية التشريع الج ازئري لمعالمة التجارية عن التشريع المغربي يكمن في اختالف اقتصاد دولتين. نخمص إلى القول أن السياسة الردعية التي أقرها التشريعين الج ازئري والمغربي ال تتوافق مع طبيعة هذه الج ارئم الماسة باالقتصاد الوطني، حيث يجب تعديل العقوبات وتكييفها مع األوضاع االقتصادية الجديدة من خالل تشديدها. Abstract: The aim of this study is to analyse and compare the penal protection against crimes against the brand in Algeria and Morocco in this regard. The study aims to learn about the legal nature of the protected brand and the impact of these crimes on the national economy of the two countries, especially in view of Algeria's and Morocco's trend towards a knowledge-based economy based on creativity and innovation. Initially, after addressing the provisions governing the trademark by clarifying the compatibility of the two legislations, the study means analysing and comparing the legal nature of the trademark in question from the control of its concept to the acquisition of the right to it, by clarifying its importance as an indicator of measurement of the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. The study goes on to show the intervention of Algerian and Moroccan legislators by establishing tribal and remote protectionist mechanisms to deter crimes against the trademark. The study examines here the role of provisional measures and the case for tradition as a mechanism for protecting the legal protection of the trademark in order to protect the national economy. Based on the previous two sections of the study, the latter attempts to clarify some of the economic trends adopted by Algeria and Morocco, from an economy based on quarters to an economy based on knowledge, and that the problem presented in such new circumstances lies in the extent to which protecting the trademark is linked to protecting the national economy. The study shows In this regard, the difference in Algerian trademark protection from Moroccan legislation lies in the difference in the economies of the two countries.We conclude by saying that the deterrent policy adopted by Algerian and Moroccan legislation is incompatible with the nature of these crimes, which affect the national economy. The penalties must be adjusted and adapted to the new economic conditions by tightening them. Résumé : Cette étude a pour objet le problème de la protection pénale de la marque commerciale en Algérie et au Maroc. Elle vise à faire connaitre l’importance économique de la marque protégée et l’impact économique des crimes dans les deux pays compte tenu de la tendance de ces deux pays à adopter une économie de créativité et d’innovation. L’étude consiste en la comparaison et en l’analyse juridique de la marque de l’adaptation de son concept à l’acquisition du droit à celle –ci après clarification de son importance en tant qu’indicateur de mesure de l’économie nationale. L’étude montre ensuite l’impact des législation algériennes et marocaines qui établissent des mécanismes visant à la protection à distance afin de dissuader tout crime contre la marque. Le rôle des mesures provisoires et aussi examine dans cette étude ainsi que l’action en contrefaçon en tant que moyen de protection juridique de la marque. Afin que protéger l’économies nationale. En outre, cette étude essaye d’illustrer certaines des tendances économiques algériennes d’une économie basée sur la rente vers une économie basée sur le savoir (créativité et innovation). Dans ces nouvel es circonstances, la protection des marques et liée à la protection de l’économie nationale. A cet égard, la protection de la marque commerciale en Algérie diffère de celle du Maroc du fait de la différence des économies des deux états algériens et marocains. Nous concluons que la politique de dissuasion adoptée par les législations algérienne et marocaine est incompatible avec la nature de ces crimes, qui affectent l’économie nationale. Les sanctions doivent être ajustées et adaptées aux nouvelles conditions économiques en les resserrant.
Keywords: Action pénale; Contrefaçon; Criminal case; Droit algérien; Droit marocain; Enregistrement; Fake; Marque commerciale; Mesures conservatoires; Procedures conservatory; Protection pénale; Registry; Trademark

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

La protection des savoirs traditionnels dans le secteur alimentaire - Vo, Nguyen Hoang Phuc (Université Lumière Lyon 2, 2023)
Les savoirs traditionnels dans le secteur alimentaire se comprennent comme le fruit d’une activité intellectuelle, d’expériences, de moyens spirituels ou d’idées, sous forme d’expressions verbales ou écrites, dans ou à partir d’un contexte traditionnel. Ils se présentent au cœur de presque toutes les activités, depuis la culture, l’élevage, la préparation et la préservation, jusqu’à la consommation des denrées alimentaires pour la destination de l’ingestion humaine, ainsi que leurs artefacts, c’est-à-dire les plats cuisinés et les produits alimentaires. Tandis qu’ils méritent d’être sauvegardés, à l’heure actuelle, ils ne font pas encore l’objet d’une protection appropriée et efficace.La thèse intitulée « La protection des savoirs traditionnels dans le secteur alimentaire » porte en premier lieu, sur la recherche d’un ou de plusieurs outils existants susceptibles d’être évoqués pour protéger les savoirs alimentaires, y compris la protection fondée sur la nature de l’objet de propriété et celle sur la nature culturelle des savoirs traditionnels dans le secteur alimentaire. Parmi les outils existants, on peut se tourner vers la propriété intellectuelle, les signes de l’origine et de la qualité, mais aussi d’autres droits plus particuliers, notamment issus des conventions internationales relatives aux droits culturels (première partie). En second lieu, partant de l’état des lieux relatif aux outils existants et du constat de leur insuffisance ou leur inaptitude à protéger de manière suffisante les savoirs alimentaires traditionnels, nous formulerons des propositions permettant d’améliorer la protection des savoirs alimentaires.
Keywords: AOP; Appellations d'origine; Droit culturel; IGP; Indication géographique; Indications géographiques protégées; Intellectual property; Patrimoine culturel immatériel; Produits du terroir; Propriedade intelectual; Propriété intellectuelle; STG; Savoirs alimentaires; Savoirs traditionnels

O segredo de negócio como direito de propriedade industrial em sentido estrito - Kilmar, Sofia Gavião (Universidade de São Paulo, 2023)
A presente tese de doutorado aborda a hipótese de segredo de negócio enquanto direito de propriedade industrial em sentido estrito. A introdução do trabalho versa sobre a relevância dossegredos de negócio na prática empresarial. Por sua vez, o Capítulo 1 é dedicado à disciplina jurídica dos segredos de negócio como atualmente firmada. Aborda, nesse sentido, as propostas de justificativa apresentadas para fundamentar a proteção jurídica conferida aos segredos de negócio. Em sequência, o Capítulo 2 do trabalho trata dos problemas observados em referidas propostas de justificativa da proteção a segredos negociais, demonstrando como as citadas propostas se mostram insuficientes e inadequadas para tanto. O Capítulo 2 também aborda como a insuficiência e inadequação das citadas propostas é prejudicial, pois gera insegurança jurídica. O Capítulo 3 apresenta a hipótese da tese, de justificativa de proteção aos segredos de negócio enquanto um direito de propriedade industrial em sentido estrito, equiparável, enquanto tal, a direitos de propriedade industrial já reconhecidos, como patentes, marcas e desenhos industriais. Para tanto, o Capítulo 3 aprofunda os conceitos de Direito de Propriedade Intelectual, de Propriedade Industrial, bem como as justificativas para a existência jurídica de direitos de Propriedade Industrial. Apresenta, ao final, a hipótese objeto da tese. Por fim, a conclusão traz considerações finais acerca do tema.
Keywords: Civil liability; Concorrência desleal; Contracts; Contratos; Industrial property; Intellectual property; Private property; Propriedade industrial; Propriedade intelectual; Propriedade privada; Propriété industrielle; Responsabilidade civil; Secret commercial; Segredos de negócio; Trade secrets; Unfair competition

Les œuvres automatisées à l'épreuve du droit d'auteur : réflexions sur les créations réalisées par des systèmes d'intelligence artificielle - Fandiño López, Efraín (Université Paris Cité, 2023)
Les progrès de l’intelligence artificielle issus de la croissance de la puissance de calcul, des mégadonnées et des nouveaux algorithmes de plus en plus puissants ont permis l'automatisation de certaines activités intellectuelles humaines. Les créateurs sont donc directement concernés, car il est désormais possible d'automatiser le processus d’exécution de création humain. Ainsi, Il convient donc d'effectuer une étude approfondie sur les oeuvres automatisées afin de déterminer si elles sont conformes au droit d'auteur et, si ce n'est pas le cas, si le droit d'auteur doit être adapté pour s’adapter à ce nouveau phénomène. Cette étude soulève plusieurs questions fondamentales, notamment celle de savoir si une œuvre automatisée est licite et comment évaluer son originalité. Elle suscite également une interrogation quant au statut de l'auteur de l'œuvre automatisée. Ces problématiques sont davantage importantes, en raison de l'utilisation croissante des systèmes d'IA en tant qu'outils de création.
Keywords: Artificial Intelligence; Arts; Automated creations; Automated works; Copyright; Creaciones automatizadas; Créations automatisées; Derechos de autor; Droit d'auteur; IA générative; Inteligencia artificial; Inteligência artificial; Intellectual property; Intelligence artificielle; Intelligence artificielle générative; New technologies; Nouvelles technologies; Nuevas tecnologías; Oeuvres automatisées; Propriété intellectuelle; Technologie et arts

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

La production de l’intelligence artificielle comme objet du droit d’auteur - Billion, Arnaud (Université Jean Moulin Lyon 3, 2023)
Les systèmes dits d’intelligence artificielle peuvent obtenir des produits dont on se demande s’ils sont éligibles au droit d’auteur. Face à cette question, le juriste intellectualiste ne peut se contenter d’un modèle grossier de son droit, ni se satisfaire d’une approximative revendication. Il est alors invité à considérer la production artificielle de manière réaliste, dans ses caractères sériels et divergents. Ceci éloigne la possibilité d’une appréciation erronée des faits : il n’y a pas, le plus souvent, un produit créé par un utilisateur de l’IA. La production artificielle, ce sont avant tout des surnuméraires, outputs obtenus incidemment en très grand nombre, traces numériques d’une ingénierie indirecte et hautement itérative. Pratiquer l’exercice de qualification au droit d’auteur sur le cas artificiel fait comprendre les raisons de l’impossible protection : les choix libres ne peuvent être qualifiants que des formes originales créées (les logiciels) … ils ne sauraient qualifier toute forme lointainement obtenue. Face à ce cas limite, les caractères de l’œuvre de l’esprit se révèlent dans la cohérence du droit positif : la conception réalisée, la disqualification du fait d’une trop grande contrainte technique, la précision et l’objectivité de l’identification et les autres conditions d’entrée au droit d’auteur, viennent souligner la détermination autoriale, la convergence créative et l’intelligibilité sociale comme le sous-texte pré-conditionnel de l’institution.
Keywords: Algorithm; Algorithme; Artificial Intelligence; Artificial production; Author’s right; Computer-Generated work; Conception and realization; Conception assistée par ordinateur; Conception réalisée; Copyright; Creativity; Création; Création assistée par ordinateur; Cybernetics; Cybernétique; Droit d'auteur; Free choices; Inteligência artificial; Intellectual property; Intelligence Artificielle; Intelligence artificielle; Liberté créative; Logiciel; Originality; Originalité; Production artificielle; Software; Work of authorship; Œuvre de l’esprit

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

Contribution à l'étude de la propriété littéraire et artistique à partir d'Internet - Monnier, Valentin (Université de Montpellier, 2022)
Le modèle propriétaire est-il le plus adapté à la réservation des œuvres de l’esprit au regard des enjeux liés à Internet ? Telle est la question à laquelle se propose de répondre cette thèse en opérant une critique du régime propriétaire encadrant les droits de l’auteur. Si la mise en œuvre d’une propriété relative aux œuvres de l’esprit apparaissait initialement justifiée, l’émergence d’Internet suscite une profonde remise en cause de ce mode de réservation. Les créations pouvant être reproduites et diffusées sans frein, l’exclusivité induite par la propriété n’apparaît plus aussi légitime en droit de la création immatérielle. Ce constat s’avère d’autant plus évident lorsque se trouve mis en exergue le développement de droits fondamentaux culturels au profit du public. Dès lors, ces éléments démontrent que la propriété littéraire et artistique ne remplit pas pleinement la finalité sociale qui devrait être la sienne. Par conséquent, cette étude invite à évaluer l’opportunité d’un régime non-propriétaire en droit de la création immatérielle. Given the stakes linked to Internet, is the ownership model the most suited to thereservation of intellectual works? This thesis aims to answer this question by criticizing theproprietary regime governing the rights of the author. If the implementation of an ownership related to the works of the mind initially appeared legitimate, the emergence of Internet causes a deep questioning of this mode of reservation. This is particularly relevant for the exclusivity induced by ownership as creations can be reproduced and disseminated without restraint. This observation is all the more significant when one takes into account the development of fundamental cultural rights for the public benefit. Therefore, these elements show that literary and artistic property does not fully fulfil the social function it should serve. Consequently, this study invites to evaluate the opportunity of a non-proprietary regime in the immaterial creation law
Keywords: Droit d'auteur; Droit des biens; Droits de l'homme; Droits fondamentaux; Fonction sociale du Droit; Fundamental rights; Intellectual property; Literary and artistic property; Property law; Propriété intellectuelle; Propriété littéraire et artistique; Social function of law; Utilitarianism; Utilitarisme

As marcas e a exclusividade na Fashion Law - Arrosi, Letícia Soster (Universidade de São Paulo, 2022)
Este trabalho trata-se de uma pesquisa feita por meio da abordagem dedutivo-dialética com a finalidade de conceituar e analisar o mercado da moda para esclarecer como os direitos intelectuais podem ser violados nesta esfera e, portanto, descobrir qual a melhor forma de proteção a ser aplicada pelos agentes econômicos deste mercado sem prejudicar a inovação em relação às marcas e aos direitos de exclusividade no mundo globalizado. As criações de moda podem ser protegidas tanto pela Propriedade Industrial quanto pelo Direito Autoral. O tipo de proteção deve ser escolhido de acordo com as características da criação e da perenidade que o criador pretende dar à obra. Cópias fazem parte da indústria e impulsionam a inovação até certo ponto ao passo que, em determinado grau, tornam-se nocivas ao mercado e prejudicam não somente os criadores, mas também toda a sociedade. Foi analisado como o nível de proteção regula os investimentos do mercado. Também foram estudados os direitos de exclusividade pelo enfoque dos direitos autorais e da Propriedade Industrial, bem como as vantagens e desvantagens da adesão do Brasil ao Protocolo de Madrid, com análise de casos envolvendo marcas estrangeiras no país e marcas brasileiras no exterior. This work is a research done through the deductive-dialectical approach with the purpose of conceptualizing and analyzing the fashion market to clarify how intellectual property rights can be violated and, therefore, discover the best form of protection to be applied by the players of this market without harming innovation, in relation to brands and exclusivity rights in the globalized world. Fashion creations in Brazil can be protected by both Trademark and Copyright. The type of protection must be chosen according to the characteristics of the creation and the perpetuity that the creator intends. Copies are part of the fashion industry and drive innovation to a certain extent, while to a certain degree they become harmful to the market and harm not only the creators but also the whole society. It will be analyzed how the level of protection regulates market investments. Exclusivity rights will also be studied from the perspective of copyright and Trademark, as well as the advantages and disadvantages of Brazil's accession to the Madrid Protocol, with an analysis of cases involving foreign brands in the country and Brazilian brands abroad.
Keywords: Brands; Direito Autoral; Exclusivity; Fashion; Globalização; Intellectual property; Marcas comerciais; Marque commerciale; Moda; Mode; Propriedade industrial; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle

L'originalité, unique condition à la protection du droit d'auteur : vérification par l'application aux créations audiovisuelles - Sougy, Théo (Université Jean Moulin Lyon 3, 2022)
Les conditions traditionnelles de la protection du droit d’auteur et les concepts d’idée, de forme et d’originalité, qu’elles induisent, sont en crise. Comment en effet distinguer l’idée de la forme, seule à pouvoir donner prise au droit d’auteur, en particulier dans une création audiovisuelle ? L’originalité, qui implique la recherche de la personnalité de l’auteur dans son œuvre lorsqu’elle est envisagée de manière subjective, ne semble quant à elle pas davantage adaptée aux créations de l’audiovisuel qui résultent souvent de la collaboration de nombreux auteurs. Le législateur français étant peu intéressé par cette crise majeure, il revint au juge et à la doctrine de caractériser avec justesse les limites de la protection du droit d’auteur. La tâche n’était pas facile, elle est rapidement devenue impossible suite aux nombreux débats doctrinaux et judiciaires, d’une part sur la pertinence de la dichotomie idée-forme, d’autre part sur les contours même de la condition d’originalité. Et finalement, c’est le juge de la Cour de justice de l’Union européenne qui va décider d’affirmer une condition d’originalité modernisée par le recours au critère des choix libres et créatifs et accompagnée d’une exigence d’expression. Le renouveau européen de la condition d’originalité devrait enfin permettre de mettre un terme à cette crise nourrie des interminables débats sur les limites de la protection du droit d’auteur. Cette originalité est désormais adaptée aux créations audiovisuelles, lesquelles souffraient particulièrement de l’imprécision des conditions traditionnelles à la protection du droit d’auteur.
Issue: 2022LYO30042
Keywords: Audiovisual; Audiovisuel; Auteur; Author; Documents audiovisuels; Droit d'auteur; Expression; Form; Forme; France; Idea; Idée; Intellectual property; Oeuvre; Originality; Originalité; Originalité (esthétique); Pays de l'Union européenne; Propriedade intelectual; Propriété intellectuelle; Work

El escrito preventivo - Molina López, Florencio (Universitat de Barcelona, 2022)
Este trabajo tiene por objeto el analísis jurídico de la figura del escrito preventivo: su origen alemán y un breve estudio comparado; la aplicación y soluciones dadas por nuestros juzgados mercantiles antes y después de su reconocimiento legal en España con el art. 132 de la Ley 24/2015, de 24 de julio, de Patentes, así como los diversos problemas que la interpretación y aplicación del mismo ha producido hasta ahora. En especial, la resoluciones judiciales dictadas en el contexto de ferias comerciales o congresos profesionales, como Mobile World Congress de Barcelona; o de aquellas que lo han aplicado más allá del ámbito material legal y tradicional de las patentes.De lege ferenda, se hacen dos propuestas alternativas: una de regulación en España de los escritos preventivos con un registro público y electrónico para la gestión de los mismos; otra de regulación de los escritos preventivos sin registro electrónico pero mejorando la redacción técnica de su regulación legal. Y, en ambos casos, bajo el presupuesto de la incorporación de este mecanismo procesal en la Ley de Enjuiciamiento Civil.
Keywords: Brevets; Ciències Jurídiques; Commercial law; Derecho de patentes; Derecho mercantil; Dret de patents; Dret mercantil; Econòmiques i Socials; Intellectual property; Medidas cautelares; Mesures cautelars; Patent laws and legislation; Propriedade intelectual; Provisional remedies

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

Nanotechnologie(s), propriété intellectuelle et droits de l'homme - Kav Goseberg, Banu (Université Côte d'Azur, 2022)
Le monde de la nanotechnologie, le monde de l’infiniment petit, évolue rapidement. Cette branche relativement nouvelle des sciences attire de plus en plus l’intérêt de scientifiques, des entreprises, des Etats mais aussi celui de tout le monde. Il y a des nouveautés tous les ans et énormément d’argent et de temps de recherche est investi dans ce domaine. Le marché de la nanotechnologie en 2020 est estimé à plus de 70 milliards de dollars et grandit rapidement tous les ans. Le droit de la propriété est plus ancien. Les principes de base et les instruments de protection ont été mis en place bien avant l’arrivée de la nanotechnologie. Le droit de la propriété intellectuelle se veut universel et neutre et a été développé sans se concentrer sur certaines inventions, technologies ou œuvres en particulier. Dans ce contexte, il faut se demander comment protéger les nouveaux développements nanotechnologiques et les investissements et si le droit de la propriété intellectuelle propose suffisamment d’instruments. La question se pose si le droit existant peut être appliqué aux inventions de la nanotechnologie et comment le faire. Il faut rechercher comment le droit de la propriété intellectuelle peut à la fois protéger les intérêts des propriétaires et en même temps faire bénéficier la société du progrès scientifique. Également, vu que la nanotechnologie concerne en grande partie le développement des médicaments et d’autres dispositions médicales, l’environnement, la surveillance, le développement durable et les intérêts et risques pour les générations futures, la question de l’éthique et des droits de l’homme se pose. Il faut arriver à trouver un équilibre entre les intérêts financiers des investisseurs et le progrès scientifique et technique qui doit bénéficier sans distinctions aux riches et aux pauvres. Ici, le droit joue un rôle fondamental pour arriver à des solutions justes pour tout le monde.
Keywords: Droits de l'homme; Intellectual property; Nanotechnologie; Propriedade intelectual; Propriété intellectuelle

Le principe de proportionnalité en droit de la propriété intellectuelle - Amat, Quentin (Université Paris 12, 2022)
Le principe de proportionnalité recouvre un champ d’application large, découlant de la protection des droits fondamentaux, dont la propriété intellectuelle fait indéniablement partie. Sa mise en œuvre, par plusieurs types de contrôles de proportionnalité, a bouleversé les certitudes doctrinales et enclenché une réflexion relative à la motivation et l’interprétation juridique. Le plus discuté desdits contrôles de proportionnalité est celui utilisé en cas de conflit fondamental. Son impact au niveau judiciaire s’est fait en plusieurs étapes. Il a pour origine la jurisprudence des deux cours européennes, elle-même inspirée du principe de proportionnalité allemand. La Cour européenne des droits de l’homme et la Cour de justice de l’Union européenne ont développé leurs propres contrôles de proportionnalité pour résoudre un conflit entre droits fondamentaux. Si la première entreprend une démarche plus concrète que la seconde, liée à la nature de sa mission, ces deux juridictions confirment toutes deux le caractère non absolu du droit de la propriété intellectuelle et la nécessité de le concilier avec les autres droits fondamentaux (reconnus par la Convention européenne des droits de l’homme et la Charte des droits fondamentaux de l’Union européenne). Lors de leur contrôle de proportionnalité, les deux cours réservent une certaine marge d’appréciation aux États membres mais donnent des indications afin de le réaliser à leur tour. Au-delà du développement d’un test en trois étapes (adéquation, nécessité et proportionnalité stricto sensu), les cours européennes révèlent des éléments à prendre en compte selon le droit fondamental opposé au droit de la propriété intellectuelle et les faits de l’espèce (type de discours en cause pour la liberté d’expression invoqué pour une utilisation d’un bien intellectuel hors des exceptions légales ; durée, complexité, coût, nécessité pour la liberté d’entreprise ou le droit à la vie privée invoquée pour une mesure de blocage sur internet…). La France a lancé ce processus d’adoption du contrôle de proportionnalité lors d’un conflit fondamental au niveau judiciaire le 15 mai 2015 par un arrêt de la première chambre civile de la Cour de cassation. Celle-ci impose désormais aux juges du fond d’expliquer de façon concrète en quoi la recherche d'un juste équilibre entre le droit de la propriété intellectuelle et un autre droit fondamental opposé commande la condamnation prononcée. Les premiers jugements et arrêts au fond ont appliqué cette jurisprudence de la Cour de cassation, notamment en cas de conflit de la liberté d’expression à travers la notion de nécessité d’usage. Leur motivation devrait assurément s’étoffer dans les prochaines années. En parallèle, il ne faut pas négliger le contrôle de proportionnalité de la sanction, qui découle également du principe de proportionnalité et qui a des applications déterminantes pour le contrôle lors d’un conflit fondamental. Une sanction disproportionnée pourrait menacer directement l’application et la cohérence des droits fondamentaux et ce risque rend indispensable la conjonction des deux contrôles. Si le législateur, tant national et européen, a adopté différentes mesures inspirées par la volonté de parvenir à une sanction proportionnée, le juge demeure essentiel dans l’application du principe de proportionnalité, puisqu’il choisit la sanction la mieux adaptée aux faits. L’enjeu est central pour le droit de la propriété intellectuelle en ce qu’il offre une grande variété de sanctions, tant pénales que civiles, afin de lutter contre la contrefaçon. Cependant, son application reste timide, autant que son intérêt pour la doctrine. Cette application est appelée à se développer davantage à travers la jurisprudence.
Keywords: Conflits de droits fondamentaux; Droit; Intellectual property; Law; Proportionality; Proportionnalité; Proportionnalité (droit); Propriedade intelectual; Propriété intellectuelle; Propriété intellectuelle (droit européen)

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

Le droit face aux technologies disruptives : le cas de la blockchain - Labbé, Thibaut (Université de Strasbourg, 2021)
La place de l’informatique dans nos sociétés actuelles est indiscutable, et ne fait que se renforcer au quotidien. Sans cesse, des technologies de l’information et de la communication poussent nos conceptions juridiques et sociales dans de nouveaux retranchements. Faire face à ces technologies signifie alors de pouvoir appréhender ces changements, et les accompagner. Pouvoir construire un raisonnement reproductible à l’essor de toute nouvelle technologie devient alors indispensable pour pouvoir anticiper ces changements induits et déterminer l’opportunité ou non de réguler. Depuis plus de 10 ans, la blockchain, protocole informatique, peut bouleverser nos systèmes actuels, qu’ils soient financiers ou juridiques. Pourtant, déconnecter l’outil de l’application est essentiel pour sa bonne appréhension et ne pas limiter l’innovation.Technologie pouvant faire le lien entre monde technique et juridique, elle invite à une collaboration entre deux mondes qui restent et seront toujours liés.
Keywords: Blockchain; Data governance; Database law; Droit des bases de données; Droit des logiciels; Gestion des données (systèmes d'information); Gouvernance des données; IP-IT; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Propriété intellectuelle (droit international); Software law; Technologie de rupture

Le phénomène de Big Data et le droit : pour une appréhension juridique par sa décomposition technique - Bougeard, Aurélien (Université de Strasbourg, 2021)
L’objet de cette étude est d’entreprendre l’appréhension juridique du phénomène de Big Data. Il s’agit ici d’un travail de recherche transdisciplinaire de ce phénomène afin de comprendre les raisons de sa formation, sa mise en place, son exécution et sa pérennité dans l’espace numérique. Cette approche transdisciplinaire autorise et facilite une meilleure compréhension pour le Droit de ce qu’est le Big Data. Ainsi, l’appréhension du Big Data par le domaine juridique est rendu possible notamment par l’analyse et l’étude du suivi de la circulation des données dans l’espace numérique. Plus précisément, l’étude de cette circulation permet de comprendre et d’observer les différentes étapes successives qui dans un schéma ayant vocation à former une boucle concourt à la survenance du Big Data en tant que phénomène.
Keywords: Big Data; Computer law; Data; Données; Données massives – Droit; Droit de l’informatique; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Propriété intellectuelle (droit international); Protection de l'information (informatique) – Droit; Theory; Théorie

Investissement et propriété intellectuelle - Dépinoy, Anaïs (Université de Lille, 2021)
La thèse porte sur les rapports entre l’investissement dans la conception d’objets immatériels et la propriété intellectuelle. Elle interroge la vocation du droit de la propriété intellectuelle à la protection d’un tel investissement. À l’examen du droit positif, il n’est pas aisé d’identifier une réponse claire à cette question.L’existence de la protection est incertaine, alors même que la technique employée est adéquate. Discutée, elle mérite d’être repensée. Son avenir dépend par ailleurs de son caractère souhaitable, et donc de sa légitimité. Aussi, pour être effective, la protection doit faire l’objet d’un choix politique de société. Proposantune lecture de la propriété intellectuelle sous l’angle de sa finalité de protection de l’investissement, l’étude est menée à l’appui de la construction d’un concept juridique d’investissements immatériels. Celle-ci permet de présenter le sujet et ses problématiques de façon renouvelée, afin de dépasser les difficultés. Le résultat de l’exercice de conceptualisation, conjugué à un exercice de classification juridique de la réalité, sert de base à un essai de reconstruction prospective du système juridique de la propriété intellectuelle. Les catégories, qualifications et régimes de ce dernier sont réaménagés, pour le faire évoluer en équilibre et cohérence, vers une fonction assumée de protection de l’investissement. L’enjeu est d’aboutir à un système de protection légitime, sécurisant et fidèle à la réalité et ses attentes.
Keywords: Capital immatériel; Concept; Droit subjectif; Economic efficiency; Efficacité économique; Industrial property; Intellectual property; Investissements; Investissements immatériels; Investments; Literary and artistic property; Profitability; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle; Propriété intellectuelle (droit international); Propriété littéraire et artistique; Qualification; Rentabilité; Reservation; Risk; Risque; Régime; Réservation; Social values; Subjective right; Valeurs sociales

Noms de domaine et modes alternatifs de règlement de conflits - Pavlenko Chapuis, Radmila (Université Paris 2, 2021)
Afin de régler les litiges relatifs aux noms de domaine, l’ICANN, entité gouvernant le DNS, crée en 1999 la procédure UDRP (Uniform Domain Name Dispute Resolution Policy, en français : règlement uniforme des litiges relatifs aux noms de domaine). Il s’agit du plus connu mais également du plus controversé des modes alternatifs de règlement de conflits en ligne. Il s'inscrit dans un millefeuille procédural au sein duquel l’ICANN superpose un grand nombre de procédures destinées à prévenir ou résoudre des litiges relatifs aux noms de domaine. Cette obscure et complexe matrice que l’ICANN qualifie d’ « administrative », n'organise cependant ni le rapport de ces procédures entre elles ni avec le droit étatique. Ces dernières années, une augmentation stratosphérique des litiges sur les noms de domaine est observée, résultant de la multiplication exponentielle de l'utilisation d'Internet par l'ensemble de la population mondiale suite à la crise sanitaire. Dans ce contexte, la sécurité juridique des titulaires de droits de propriété intellectuelle invite à repenser l'organisation du règlement des litiges relatifs aux noms de domaine en le faisant bénéficier d’une réforme unificatrice. Elle offre non seulement l'opportunité de créer un système de règlement de litiges unique mais également d’en préciser la nature et de clarifier les concepts à prouver. À cette fin, nous proposons de transformer le système actuel, historiquement extrajudiciaire et par nature privé, en un processus d'arbitrage avec l'objectif d'établir un lien procédural entre le système extrajudiciaire de l’ICANN et le droit étatique ainsi que d’assurer davantage de garanties procédurales aux parties. In order to settle disputes relating to the registration of internet domain names, ICANN, the governing body of the DNS, created the Uniform Domain Name Dispute Resolution Policy (UDRP) in 1999. This is the best known but also the most controversial of the alternative methods of online dispute resolution. UDPR is a part of the arbitration structure in which ICANN imposes a process intended to prevent or resolve disputes relating to domain names. The obscure and complex matrix that ICANN qualifies as ''administrative'', does not organize the relationship of these arbitration procedures to each other or to state law. In recent years, a stratospheric increase in domain name disputes has been observed, resulting from the ten-fold increase in Internet use by the entire world population following the Covid health crisis.In this context, the legal security of the holders of Intellectual Property (IP) rights invites a rethinking of the organization of the settlement of disputes relating to domain names by proposing a unifying reform. This offers an opportunity to create a new unique dispute resolution system, and also to specify its nature and clarify the concepts to be proven. Towards this end, we propose a full reform to transform the current system, which has been historically extrajudicial and is by its nature private, into a full arbitration process, pursuing the objective of establishing a procedural link of the extrajudicial system with state law as well as to provide more procedural guarantees to all parties.
Keywords: ADR; Alternative dispute resolution; Alternative methods; Arbitrage; Arbitrage (droit); Arbitragem; Arbitraje; Arbitration; DNS; Disputes; Domain names; Extra-Judicial system; Extra-judiciaire; ICANN; Internet Corporation for Asigned Names and Numbers; Litiges; Marques de commerce; Modes alternatifs de règlement des conflits; Noms de domaine; Noms de domaine (Internet) – Droit; ODR; Online dispute resolution; Règlement de conflits; Système de règlement de litiges unique; UDRP; Unique dispute resolution system

La contrefaçon de médicaments dans l'espace U.E.M.O.A. - Ouattara, Simplice (Université de Strasbourg, 2021)
La contrefaçon de médicament à usage humain est un phénomène de dimension internationale qui constitue aujourd’hui plus qu’hier, une véritable pandémie. La réalisation de cette étude nous a amené à déterminer respectivement la caractérisation de la contrefaçon de médicaments dans l’espace UEMOA et les moyens de lutte subséquents mis en oeuvre pour l’éradication de ce phénomène. En effet, la caractérisation de la contrefaçon de médicaments dans l’espace UEMOA a consisté à identifier respectivement l’objet de la contrefaçon c’est à dire le médicament et les actes constitutifs de contrefaçon. Quant au point relatif aux moyens de lutte mis en oeuvre contre la contrefaçon de médicaments à usage humain, nous avons tenté de mettre en exergue leur inadéquation avec le délit de contrefaçon de médicament ou parfois même leur inexistence dans certains Etats membres de l’UEMOA rendant ainsi la lutte vaine au point de constituer un terreau favorable à la prolifération de ce fléau, d’où la nécessité d’exhorter ceux-ci à se doter de textes contemporains adaptés à la gravité de ce phénomène. La situation peu reluisante de l’environnement juridique dans les Etats membres de l’UEMOA relatif au délit de contrefaçon de médicament et la protection de la médecine traditionnelle, exposent les populations à la consommation de médicaments contrefaisants. Enfin, la question épineuse du rapport entre le monopole du brevet et le libre accès au médicament par les Pays les Moins Avancés (PVD) et les Pays en Voie de Développement (PVD) a été abordée. Il s’agissait pour nous de montrer la nécessité pour les Etats membres de l’UEMOA d’avoir recourt aux flexibilités prévues par les ADPIC parce qu’ils pourraient être une véritable alternative à l’accès au médicament de bonne qualité même si les Pays Développés (PD), notamment, les USA et l’UE ne leur facilitent pas toujours la tâche avec l’instauration des ADPIC Plus ou les Accords de Libre Echange (ALE) avec comme objectif de contraindre les PMA à ne pas pouvoir recourir aux flexibilités prévues à l’article 30 de l’Accord sur les ADPIC et à la Déclaration de Doha. The counterfeiting of medicines for human use is a phenomenon of international dimension which today, more than ever, constitutes a veritable pandemic. The realization of this study led us to determine respectively the characterization of counterfeit drugs in the UEMOA area and the subsequent control means implemented for the eradication of this phenomenon. In fact, the characterization of counterfeit medicines in the UEMOA area consisted in identifying respectively the object of the counterfeit, in the medicine and the acts constituting counterfeit. As for the point relating to the means of combating the counterfeiting of medicines for human use, we have tried to highlight their inadequacy with the offense of counterfeiting medicines or sometimes even their non-existence in certain UEMOA member states. thus the vain struggle to the point of constituting a breeding ground for the proliferation of this scourge, hence the need to urge them to equip themselves with contemporary texts adapted to the gravity of this phenomenon. The gloomy situation of the legal environment in the UEMOA member states relating to the offense of counterfeiting drugs and the protection of traditional medicine, exposes populations to the consumption of counterfeit drugs. Finally, the thorny issue of the relationship between the patent monopoly and free access to medicines by the Least Developed Countries (DCs) and Developing Countries (DCs) was addressed. For us, it was a question of showing the need for the member states of UEMOA to have recourse to the flexibilities provided for by the TRIPS because they could be a real alternative to access to good quality medicine even if the countries Developed (PD), in particular, the USA and the EU do not always facilitate their task with the establishment of the TRIPS Plus or the Free Trade Agreements (FTA) with the objective of forcing the LDCs not to be able to use flexibilities provided for in Article 30 of the TRIPS Agreement and the Doha Declaration.
Keywords: ADPIC; Afrique occidentale; Brevets; Contrefaçon; Contrefaçon de médicaments; Counterfeiting; Droit international privé; Facilitation; Falsification; Flexibilities; Flexibilités; Intellectual property; Marks; Marques; Medicines; Médicaments; OAPI; Patents; Propriedade intelectual; Propriété intellectuelle; UEMOA; Union économique et monétaire Ouest africaine

Les exploitants des propriétés intellectuelles - Pasco, Jean-Christophe (Université de Poitiers, 2021)
L’exploitation des propriétés intellectuelles est un phénomène peu étudié dans la doctrine. Principalement appréhendée sous l’angle économique, elle est alors cantonnée à une perspective entrepreneuriale, stratégique ou limitée à la question de la contrefaçon. Suivant le même mouvement, l’analyse des exploitants est trop souvent laissée pour compte, ce qui perpétue de fausses représentations vis-à-vis de cet acteur clef, réduit trop souvent à un entrepreneur univoque. Cette thèse propose une grille d’analyse prenant les créations comme point de départ – les inventions et les œuvres – pour ensuite construire les schémas ainsi que les modèles d’exploitation des droits les appréhendant – le titre et le droit d’auteur. Une conclusion intermédiaire s’impose alors : à une architecture linéaire des relations entretenues par l’exploitant, fondée sur les perspectives commerciales de l’exploitation en droit des brevets, s’oppose une architecture complexe dans laquelle l’intervention de l’exploitant de droits d’auteur est « intermédiée » et fonctionnellement déterminée, le plaçant au cœur d’une situation dédoublée. À la lumière de ces analyses, nous portons un regard renouvelé sur les obligations apparemment communes aux deux régimes : l’obligation d’exploiter, l’obligation de verser une contrepartie – un prix, une redevance ou une participation – et l’obligation de rendre compte. Il en ressort une construction obligationnelle spécifique à chaque modèle d’exploitants, en termes de contenu mais encore de hiérarchie de ces obligations. Ce qui alimente un peu plus la thèse de la pluralité des modèles dans le débat de fond relatif à l’avenir des propriétés intellectuelles.
Keywords: Accountability; Communication; Communication de l’œuvre; Compte-rendu; Entrepreneurial risk; Exclusive right; Exclusivité; Exploitation; Exploiting parties; Intermédiaire; Invention; Monopole d’exploitation; Obligation to operate; Operating monopoly; Participation; Price; Prix; Proportional sharing of the income; Risques; Régimes des exploitants; Secret; Speculation; Spéculation; Structure obligationnelle; Valeurs des créations; Values of creations

La notion de marque renommée - Nahum, Anaïs (Université Paris-Dauphine, 2020)
Le présent travail propose une étude approfondie de la définition de la marque renommée et de la protection dont elle bénéficie à l’heure actuelle au niveau national, à la lumière du nouveau contexte européen et international.
Keywords: Civil liability; Concurrence déloyale; Contrefaçon; Counterfeit; Dilution; Fame; Famous trademark; Fonction de la marque; Fonction performative; Free-riding; Marque; Marque notoire; Marque renommée; Marques de commerce; Parasitisme; Performative function; Produits commerciaux – Faux; Profit indu; Renommée; Reputation; Responsabilité civile; Responsabilité du fait des produits; Réputation; Trademark; Trademark function; Unfair advantage; Unfair competition; Well-Known trademark

Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Lex loci protectionis et droit d'auteur - Aba'a Megne, Harry (Université Côte d'Azur, 2020)
Le principe de territorialité domine la matière de la propriété intellectuelle et en particulier celle du droit d’auteur. Si ce principe et la règle de conflit qu’il inspire, la lex loci protectionis, constituaient de véritables avancées à la fin du XIXème s., de nos jours, ils peinent à convaincre. En effet, le principe de territorialité qui est rattachable au principe de souveraineté dans sa dimension de régulation de l’ordre juridique interne subit de multiples remises en cause. Or, en raison de l’intensification des échanges transnationaux, de l’extension des marchés, de la montée des pouvoirs privés économiques, de l’exploitation dématérialisée des œuvres et notamment, la possibilité de les diffuser sur des réseaux mondiaux comme internet, la souveraineté tend à perdre en puissance. Cela oblige à questionner la pertinence d’un rattachement territorial vis-à-vis de réalités a-territoriales. Le maintien tel quel du principe de territorialité, en termes de conflit de lois, atteint alors la sécurité juridique et les attentes légitimes des parties. Le parti pris de ces travaux est celui d’une réévaluation. Il ressort en effet que le recul dans les relations transnationales du principe de souveraineté - qui sous-tend le principe de territorialité - devrait se traduire sur le plan de la règle de conflit, par un recul de ladite territorialité. A rebours de la tendance générale qui consacre l’hégémonie de la lex loci protectionis, les présents travaux proposent d’une part, d’en circonscrire la compétence dans les domaines où le principe de territorialité ne s’impose pas comme une nécessité, et d’autre part de réorienter le rattachement de manière à limiter la concurrence des lois applicables. Il s’agit, en d’autres termes, de réserver une place à l’universalisme compris comme un rempart contre la variabilité du droit applicable et l’insécurité juridique que cette variabilité pourrait emporter.
Keywords: Compétence territoriale; Convention de Berne; Droit international privé; Droits d'auteur; Intellectual property; Lex loci protectionis; Principe de territorialité; Propriedade intelectual; Propriété intellectuelle

Le contrat d'édition - Tayar, Tewfek (Université Paris Cité, 2020)
Le contrat d'édition est la convention la plus ancienne du droit d'auteur. Qualifié de "prototype" des contrats d'auteur par la doctrine spécialisée, le contrat d'édition bénéficie d'un régime rigoureux au sein du Code de la propriété intellectuelle. Pourtant, les évolutions de ces dernières décennies induites par le progrès numérique, par l'industrialisation mondialisée de la culture et par le renouveau progressif du droit civil des contrats, ont largement remis en cause la vigueur et la légitimité de cette institution pluri séculaire. Actuellement, le contrat d'édition apparaît dépassé par sa propre rationalité. Ainsi, la conjonction des différents enjeux précités justifie la tenue d'une étude renouvelée de ce contrat qui contribuera en outre à la cohérence du droit des contrats d'auteur.
Keywords: Common interests; Contrat d'édition; Contrat fiduciaire; Copyright; Digital; Droit d'auteur; Fiduciary contract; Gestion des droits numériques; Intellectual property; Intérêts communs; Numérique; Ordre public; Partie faible; Propriedade intelectual; Propriété intellectuelle; Publishing agreement; Relations écrivains-éditeurs

Droit d'auteur et accès à la connaissance - Dongmo, Joël (Université de Nantes, 2020)
L’effervescence intellectuelle et culturelle qui caractérise le siècle des Lumières favorise l’éclosion d’un public friand de connaissances. Cette demande s’additionne à la nécessité pour les auteurs de vivre de leurs créations pour constituer le cadre dans lequel le droit d’auteur a été conçu. Les réflexions philosophiques et juridiques qui ont permis la conceptualisation de ce droit posent le caractère consubstantiel du lien entre le droit d’auteur et l’accès à la connaissance. Ce lien qui se confirme encore lors de sa consécration est remis en cause sous l’effet des pratiques du droit d’auteur dans le numérique. La mise en œuvre de la protection octroyée par ce droit dans un tel contexte semble justifier des pratiques de nature à remettre en cause la relation entre le droit d’auteur et l’accès à la connaissance. Il apparaît alors que la légitimité de ce droit est intimement liée à sa faculté à favoriser l’accès à la connaissance. L’équilibre que le droit d’auteur garantit entre les intérêts du public et ceux des auteurs se présente comme un élément essentiel de sa justification. Même si les sources de la crise du droit d’auteur se trouvent, pour la plupart d’entre elles, dans l’exploitation au sein de l’univers numérique des œuvres protégées, le renouvellement de ce droit peut emprunter la même voie. Dans ce sens, des initiatives qui s’inscrivent dans le mouvement de l’accès libre s’orientent vers un meilleur accès à la connaissance via les œuvres à caractère scientifique ou pédagogique en exploitant les possibilités offertes par l’univers du numérique. Dans le même temps, l’américanisation du droit d’auteur pourrait permettre l’introduction d’une certaine dose de souplesse dans le droit d’auteur à condition que ce phénomène accentué par la révolution numérique ne dévoie pas ce droit en le « dépersonnalisant ». The intellectual and cultural effervescence that characterizes the enlightenment century fowours the blossoming of a public fond of knowledge. This demand, more and more higher added to the necessity for authors to live off the fruit of their creations constitute the framework in which copyright has been conceived. Thus, the environment in which philosophical and legal considerations have permitted the conceptualization of this rink between copyright and the access ton knowledge. This link definitely confirms itself through the consecration of this right is questioned under the impulsion of copyright practices namely the digital one. The implementation in this context of the protection granted by this right seems to justify practices that can question the relationship between copyright and the access to knowledge. It therefore appears that the legitimacy of this right is closely linked its faculty to favour access to knowledge. Thus, the balance that copyright maintains between public interest and those of authors presents itself as an essential element of its justification. Although the source of the crisis of copyright are found (for the vast majority) in the exploitation of the digital world of protected woks, the regeneration of this right can definitely follow the same path. In this light, initiatives that feature in this movement of the free access to knowledge through scientific or pedagogic works by exploiting precisely the possibilities offered by the digital world. In this same perspective, the americanization of copyright could enable the Introduction of a certain dose of flexibility in the copyright on the condition that this phenomenon accentuated by the digital revolution does not mislead this right by “depersonalizing” it.
Issue: 2020NANT3006
Keywords: Access to knowledge; Accès à la connaissance; Balance of interests; Culture (démocratisation); Droit d'auteur; Legitimacy; Légitimité; Société numérique; Équilibre des intérêts

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

La cotitularité de droit de propriété intellectuelle en droit OAPI - Houangni Houssokpo, Valérie Eméfa (Université d'Abomey-Calavi, 2020)
Le cotitulaire est celui qui, au même titre qu’un ou plusieurs autres, est investi du même droit. Cette idée de détention de droit ou de titularité de droit est accentuée par la nature incorporelle ou immatérielle de la “chose’’ création intellectuelle. Juridiquement en effet les choses incorporelles et plus encore la création intellectuelle semblent se réduire à chacun des droits portant sur elles pendant que seul le droit de propriété saisit la totalité de la chose, de la chose corporelle. La nature de droit réel sur une “chose’’ immatérielle, droit non absolu, droit différent de la propriété de droit commun sur cette chose a été révélée et retenue. Lorsqu’on analyse alors la cotitularité du droit de propriété intellectuelle, c’est-à-dire lorsqu’on se situe au niveau du droit, de la relation interne entre un sujet et son objet, que ce sujet ne peut exclure deux ou trois autres, et ce, de façon définitive, le problème n’est pas seulement au niveau de l’exclusivité des parts telle que régie par le régime de l’indivision du Code civil. Il se pose une question d’exercice du même droit entre personnes titulaires de ce droit unique et égal entre eux, question non réglée, voire soigneusement éludée par ce texte. Les cotitulaires du droit de propriété intellectuelle font son acquisition ensemble pour pouvoir en bénéficier, pas pour avoir une part de la création intellectuelle, chose immatérielle. La présente thèse démontre l’inapplicabilité du régime de droit commun de l’indivision aux droits de propriété intellectuelle et montre que le contrat est le seul régime d’exercice du droit de propriété intellectuelle en situation de cotitularité de droit.
Keywords: Cotitulaire; Cotitularité de droit; Droit OAPI; Intellectual property; Propriété intellectuelle; Régime juridique; Titulaire; Titularité de droit